Oxcarbazepine may be an effective option for Chinese pediatric patients with self-limited focal epilepsy of neonatal/infantile onset: a retrospective cohort study - Sun, Na; Wang, Xueying; Huang, Shaoping; Yang, Lin; Li, Dan (Frontiers in Pediatrics, 2025)
ObjectiveThe aim of this study was to evaluate the long-term follow-up data of Chinese children with self-limited focal epilepsy with neonatal/infantile onset (SeLFE) and to investigate the clinical features, genetic background and treatment outcomes of this type of epileptic syndrome.MethodsWe conducted a retrospective cohort study of twenty-six children with SeLFE admitted to or followed by the Department of Pediatrics, Second Affiliated Hospital of Xi'an Jiaotong University from October 2011 to October 2021. Treatment decisions were based on the children's seizure semiology, frequency, economy, medication accessibility, allergies and other factors, and initial medications including levetiracetam, phenobarbital and oxcarbazepine. All children were followed up regularly in the outpatient clinic.ResultsThe 26 children, 13 male and 13 female, were followed for a mean of 54.0 (49.0, 58.5) months. Trio whole-exome sequencing (WES) revealed no pathogenic genetic abnormalities in 16 children, and known pathological genes including PRRT2, SCN2A and KCNQ2 were detected in 10 children. Thirteen children (50.0%) achieved complete seizure control after first-line monotherapy. Among the 12 patients who failed to respond to the first monotherapy, 9 patients achieved a seizure free status with oxcarbazepine, which was used as the second-line monotherapy or as add-on therapy. One patient recovered spontaneously without treatment.ConclusionAlthough SeLFE is often self-limited, this study showed that complete seizure control is not always achieved with initial medication therapy. Oxcarbazepine may be an effective option for the treatment of SeLFE.